2020
DOI: 10.1111/dth.14269
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of psychological state in patients with alopecia areata: A qualitative study

Abstract: Hair loss can significantly impact an individual's psychological state, self-image, and can lead to numerous personal, social, and occupational problems. Although these impairments are well documented in primary studies and reviews, and the need for appropriate psychological help is emphasized, there is still a lack of knowledge for a broader and specific picture. The patient's perspective is vital while seeking to understand the content of the variables like "impaired body image" or "low self-esteem." This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…It is extremely important to detect possible emotional problems accompanying the disease. Because pharmacological treatments are ineffective, especially in severe forms, and psychotherapeutic approaches are needed [18,19]. In a recent study, the association with psychiatric diseases was investigated and it was found that depression, anxiety and sleep disorders often accompanied the disease.…”
Section: Alopecia Areatamentioning
confidence: 99%
See 1 more Smart Citation
“…It is extremely important to detect possible emotional problems accompanying the disease. Because pharmacological treatments are ineffective, especially in severe forms, and psychotherapeutic approaches are needed [18,19]. In a recent study, the association with psychiatric diseases was investigated and it was found that depression, anxiety and sleep disorders often accompanied the disease.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…In addition, it has been determined that both alopecia areata and psychiatric disorders mutually affect each other and lead to disease progression. The sense of identity is severely damaged, especially in women, and feelings of grief and pain emerge [19]. While sexual identity is damaged in women, social identity is damaged by loss of trust more in men.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…Women reported loss of traits around their own humanness and thus feelings of shame, unacceptability, and impairment of social life. Men reported greater concern about the impact on their social identity, feelings of being rejected by society 60 …”
Section: Psychopathology Of Aamentioning
confidence: 99%
“…Men reported greater concern about the impact on their social identity, feelings of being rejected by society. 60 A solid and better understanding of the psychological and psychopathological mechanisms associated with AA is still required as well as the associations between the immune system, stress and the physiological and psychopathological responses need to be further explored.…”
Section: Psychopathology Of a Amentioning
confidence: 99%
“…For example, it has been separately reported that men describe less use of support groups than women and fewer attempts to cover bald patches, without further elaboration on the reasons (Hunt and McHale, 2005; Welsh and Guy, 2009). In another study, Barkauskaite and Serapinas (2020) interpreted gender differences between the qualitative accounts of four women and two men with AA in their phenomenological analysis, suggesting that the men expressed more concern about the impact of AA on their ‘social identity’ whereas the women described a broader impact on their self-concept. Clearly, these analyses were limited by only involving two men.…”
Section: Introductionmentioning
confidence: 99%